Thermosetting polyurethane neutron conversion screen and preparation method thereof

Preparation of fluorescent polyurethane prepolymers by in-situ polymerization solves the problem that existing neutron conversion screens cannot provide high brightness and high resolution at the same time, and realizes high brightness and high resolution neutron conversion screens, improving the imaging quality of neutron photography.

CN119751806AActive Publication Date: 2025-04-04INSTITUTE OF NUCLEAR PHYSICS AND CHEMISTRY CHINA ACADEMY OF ENGINEERING PHYSICS
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202411846001.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-16
Publication Date
2025-04-04
Estimated Expiration
2044-12-16

AI Technical Summary

Technical Problem

Existing neutron conversion screens cannot provide both high brightness and high resolution, resulting in poor neutron photography imaging quality.

Method used

Fluorescent polyurethane prepolymers were prepared by in-situ polymerization. By modifying the surface defects of the phosphor and achieving uniform distribution, a high-brightness and high-resolution thermoset polyurethane neutron conversion screen was prepared.

Benefits of technology

The high brightness and high resolution of the neutron conversion screen are achieved, the imaging quality of neutron photography is improved, and the problem of poor imaging quality under the conditions of low collimation than high gamma background in the prior art is overcome.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119751806A_ABST
    Figure CN119751806A_ABST
Patent Text Reader

Abstract

The invention discloses a thermosetting polyurethane neutron conversion screen and a preparation method thereof, zinc sulfide fluorescent powder is firstly fully dispersed in oligomerized dihydric alcohol, then an isocyanate group-terminated fluorescent powder polyurethane prepolymer is prepared by an in-situ polymerization method, and finally, the neutron conversion screen is prepared by means of curing and crosslinking of low-molecular polyhydric alcohol. The high-resolution and high-brightness thermosetting polyurethane neutron conversion screen has the advantages of high sensitivity, high resolution and the like. In the preparation of the neutron conversion screen, the feeding ratio of diisocyanate to dihydric alcohol in the in-situ polymerization process of the fluorescent polyurethane prepolymer is (2.1-3.1): 1, and the content of zinc sulfide fluorescent powder in the prepared neutron conversion screen is 50-75%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of nondestructive testing photography of neutron detectors, and in particular to a thermosetting polyurethane neutron conversion screen and a preparation method thereof. Background Art

[0002] The neutron radiography system consists of three main parts: neutron source, collimator, and image detector system (including neutron fluorescence conversion screen). The key component for detecting the spatial distribution of neutrons passing through the sample is the position-sensitive neutron detector, which is called the neutron-fluorescence conversion screen in neutron radiography technology. The neutron-fluorescence conversion screen is actually a plate-shaped functional composite material of a certain thickness. Its function is to convert the neutron rays passing through the sample to the neutrons in the conversion screen into protons of a large number of hydrogen atoms in the material and the neutrons to form recoil protons. The recoil protons make the fluorescent material emit light, thereby producing a detectable material image on the photosensitive film.

[0003] The neutron conversion screen is a key component of neutron photography, and its performance directly affects the final imaging quality. At present, in the field of neutron photography, the neutron conversion screens used mainly include mixed pressed screens composed of polyethylene, polypropylene, epoxy resin, etc. and fluorescent materials (mostly zinc sulfide (Ag) or Gd2S2O), organic scintillators containing aromatic benzene ring structures, array shifted fiber neutron-fluorescence conversion screens, etc. Among them, the scintillator screen and array shifted fiber screen have high detection efficiency (high brightness), but low resolution (above 2mm), while the mixed pressed screen has a higher resolution (below 0.5mm) and low detection efficiency (low brightness). The above three types of neutron conversion screens cannot provide satisfactory photographic effects. Summary of the invention

[0004] In view of this, the purpose of the present invention is to provide a high-brightness thermosetting polyurethane neutron conversion screen and a preparation method thereof. The surface defects of the phosphor are modified and the uniform distribution of the phosphor is achieved. Thus, a high-resolution and high-brightness thermosetting polyurethane neutron conversion screen is obtained.

[0005] The present invention provides a method for preparing a fluorescent polyurethane prepolymer by in-situ polymerization, which is characterized by comprising the following steps:

[0006] a) Raw material pretreatment:

[0007] Weigh a certain amount of polyether diol or polyester diol into a 250 ml three-necked flask, and use a water ring vacuum pump to evacuate and remove water at 110° C. for 1-2 hours; weigh a certain amount of silver-doped zinc sulfide phosphor ZnS:Ag, and place it in a vacuum oven at 80-100° C. and dry it for 1-2 hours;

[0008] b) Preparation of pre-dispersion of oligomeric diols:

[0009] Take a certain amount of processed silver-doped zinc sulfide phosphor ZnS:Ag and polyether diol or polyester diol, coupling agent, catalyst, antioxidant, dissolve them in a solvent, and fully disperse them in a high-speed disperser for 15-45 minutes to obtain a pre-dispersion of oligomeric diol, wherein the components are composed of the following weight percentages:

[0010]

[0011] c) Preparation of fluorescent polyurethane prepolymer:

[0012] A quantitative amount of fluorescent polyurethane prepolymer is weighed at room temperature and put into a reactor equipped with a reflux condenser and a stirrer, and then a pre-dispersion of diisocyanate: oligomeric diol is put into diisocyanate at a molar ratio of 2.1-3.1:1.0, stirred at room temperature -40 DEG C for 1 hour, then slowly heated to 60-80 DEG C and stirred for reaction for 2-5 hours, and nitrogen protection is used during the reaction process; the reaction is terminated, and tetrahydrofuran in the reaction mixture is removed by reduced pressure distillation with a water ring vacuum pump to obtain an in-situ polymerized fluorescent polyurethane prepolymer.

[0013] Further, the diisocyanate includes toluene diisocyanate (HDI), diphenylmethane diisocyanate (MDI), hydrogenated diphenylmethane diisocyanate (HMDI), isophorone diisocyanate (IPDI), hexamethylene diisocyanate (HDI), hexamethylene diisocyanate trimer (PHDI), lysine diisocyanate (LDI) or a combination thereof.

[0014] Furthermore, the diisocyanate is used in an excess amount of 5-55% to ensure a low polymerization degree of the prepolymer and to modify the surface of the zinc sulfide phosphor.

[0015] Furthermore, the polyether diol or polyester diol includes ethylene glycol, propylene glycol, diethylene glycol, 1,4-butanediol, phthalic acid, adipic acid, halogenated phthalic acid, polyethylene glycol, polypropylene glycol, polytetrahydrofuran diol or polyester diol prepared by esterification reaction of phthalic anhydride or a combination thereof.

[0016] Furthermore, the silver-doped zinc sulfide phosphor ZnS:Ag includes silver-doped ZnS:Ag / Mn, ZnS:Ag / Cu, ZnS:Ag / Si or a combination thereof.

[0017] The present invention provides a method for preparing a thermosetting polyurethane neutron conversion screen using the fluorescent polyurethane prepolymer, which is characterized by comprising the following steps:

[0018] a) Preparation of curing agent:

[0019] The low molecular weight polyol, the solvent, and the oligomeric diol are mixed in a weight ratio of 1:(1-2) between the low molecular weight polyol and the solvent, and the number of alcohol hydroxyl equivalents of the oligomeric diol does not exceed the number of alcohol hydroxyl equivalents of the low molecular weight polyol, and stirred and mixed at room temperature to obtain a curing agent;

[0020] b) Compounding, pouring and curing of curing system:

[0021] b1) putting the fluorescent polyurethane prepolymer into a mixer equipped with a stirrer and a vacuum pump, adding a curing agent at room temperature, stirring rapidly, and stirring for 3 minutes while vacuuming, and the overall mixing and stirring time is controlled within 10-15 minutes;

[0022] b2) pouring the stirred mixture into a square plate cavity mold with a thickness of 1-6 mm, placing the mold in a vacuum-capable closed container, evacuating the container for 30-60 minutes, and curing at room temperature (25-40° C.) for 20-72 hours;

[0023] b3) The mold is then heated to 60° C., cured for 2 hours, naturally cooled to room temperature for 6 hours, and then heated to 80° C. for 1 hour. The mold is cooled and demoulded, and the burrs are repaired and the defects are cleaned to obtain a thermosetting polyurethane neutron conversion screen.

[0024] Furthermore, the low molecular weight polyol includes glycerol, triethanolamine or a combination thereof.

[0025] Furthermore, the curing agent contains multifunctional polyols and long-chain diols, which have the function of adjusting the reaction speed and reducing the viscosity of the curing system, thereby facilitating rapid degassing.

[0026] The invention provides a thermosetting polyurethane neutron conversion screen, which is characterized in that the thermosetting polyurethane neutron conversion screen is obtained according to a preparation method of the thermosetting polyurethane neutron conversion screen.

[0027] Furthermore, the thickness of the thermosetting polyurethane neutron conversion screen is 0.5-0.8 mm. The greater the thickness, the higher the brightness, and the lower the resolution. Vice versa. Under the condition that the composition of the fluorescent polyurethane functional material is certain, the optimal balance between resolution and sensitivity can be adjusted by adjusting the thickness of the conversion screen.

[0028] In the reaction mixture composed of the above-mentioned multiple materials, diisocyanate and oligomeric diol are raw monomers for synthesizing polyurethane. The synthesized polyurethane is the base material of the conversion screen, which also plays the role of an adhesive and is also the material for neutrons to produce recoil protons in nuclear reactions; the role of zinc sulfide phosphor is to convert the energy of charged ion deposition into visible light for easy development and photography; the role of the coupling agent is to make the phosphor more evenly dispersed in the oligomeric diol; the main role of the added solvent is to reduce the viscosity of the mixture with high powder content, and the role of the antioxidant is to prevent the oxidation and discoloration of the organic polymer; the role of the catalyst is to promote the condensation reaction between diisocyanate and diol; the in-situ polymerization process adopted in the preparation process of the polyurethane prepolymer is to facilitate the uniform dispersion of the zinc sulfide phosphor at a lower viscosity before the prepolymer is formed, and to achieve surface defect modification of the zinc sulfide powder during the polymerization process to enhance its luminous efficiency. The above-mentioned percentage range of the combination of these components, as well as the process conditions of the prepolymer preparation and curing process are determined through a large number of experiments. The above-mentioned combination percentage and the thickness range of the conversion screen enable the neutron conversion screen of the present invention to have an excellent balance of high brightness, high resolution and formability.

[0029] Beneficial effects of the present invention:

[0030] The present invention provides a neutron fluorescence conversion screen and a preparation method thereof with the advantages of low cost, high brightness, high resolution, etc. The present invention can overcome the disadvantage of poor imaging quality of the existing neutron conversion screen under the conditions of low collimation ratio and high gamma background, and solve the problem that the existing neutron photography conversion screen cannot take into account both high sensitivity and high resolution at the same time. The neutron conversion screen of the present invention is of great significance for improving the quality of neutron imaging. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 Schematic diagram of the fluorescence spectra of ZnS:Ag, PU and ZSPU in Example 1 of the present invention;

[0032] Figure 2 Schematic diagram of surface detection of neutron conversion screens in Example 1 of the present invention and four types of neutron conversion screens in the prior art;

[0033] Figure 3 Luminescence brightness detection effect diagram of the neutron conversion screen of Example 1 of the present invention and four neutron conversion screens in the prior art. DETAILED DESCRIPTION

[0034] The present invention provides a method for preparing a fluorescent polyurethane prepolymer by in-situ polymerization, which is characterized by comprising the following steps:

[0035] a) Raw material pretreatment:

[0036] Weigh a certain amount of polyether diol or polyester diol into a 250 ml three-necked flask, and use a water ring vacuum pump to evacuate and remove water at 110° C. for 1-2 hours; weigh a certain amount of silver-doped zinc sulfide phosphor ZnS:Ag, and place it in a vacuum oven at 80-100° C. and dry it for 1-2 hours;

[0037] b) Preparation of pre-dispersion of oligomeric diols:

[0038] Take a certain amount of processed silver-doped zinc sulfide phosphor ZnS:Ag and polyether diol or polyester diol, coupling agent, catalyst, antioxidant, dissolve them in a solvent, and fully disperse them in a high-speed disperser for 15-45 minutes to obtain a pre-dispersion of oligomeric diol, wherein the components are composed of the following weight percentages:

[0039]

[0040] c) Preparation of fluorescent polyurethane prepolymer:

[0041] A quantitative amount of fluorescent polyurethane prepolymer is weighed at room temperature and put into a reactor equipped with a reflux condenser and a stirrer, and then a pre-dispersion of diisocyanate: oligomeric diol is put into diisocyanate at a molar ratio of 2.1-3.1:1.0, stirred at room temperature -40 DEG C for 1 hour, then slowly heated to 60-80 DEG C and stirred for reaction for 2-5 hours, and nitrogen protection is used during the reaction process; the reaction is terminated, and tetrahydrofuran in the reaction mixture is removed by reduced pressure distillation with a water ring vacuum pump to obtain an in-situ polymerized fluorescent polyurethane prepolymer.

[0042] Further, the diisocyanate includes toluene diisocyanate (HDI), diphenylmethane diisocyanate (MDI), hydrogenated diphenylmethane diisocyanate (HMDI), isophorone diisocyanate (IPDI), hexamethylene diisocyanate (HDI), hexamethylene diisocyanate trimer (PHDI), lysine diisocyanate (LDI) or a combination thereof.

[0043] Furthermore, the diisocyanate is used in an excess amount of 5-55% to ensure a low polymerization degree of the prepolymer and to modify the surface of the zinc sulfide phosphor.

[0044] Furthermore, the polyether diol or polyester diol includes ethylene glycol, propylene glycol, diethylene glycol, 1,4-butanediol, phthalic acid, adipic acid, halogenated phthalic acid, polyethylene glycol, polypropylene glycol, polytetrahydrofuran diol or polyester diol prepared by esterification reaction of phthalic anhydride or a combination thereof.

[0045] Furthermore, the silver-doped zinc sulfide phosphor ZnS:Ag includes silver-doped ZnS:Ag / Mn, ZnS:Ag / Cu, ZnS:Ag / Si or a combination thereof.

[0046] The present invention provides a method for preparing a thermosetting polyurethane neutron conversion screen using the fluorescent polyurethane prepolymer, which is characterized by comprising the following steps:

[0047] a) Preparation of curing agent:

[0048] The low molecular weight polyol, the solvent, and the oligomeric diol are mixed in a weight ratio of 1:(1-2) between the low molecular weight polyol and the solvent, and the number of alcohol hydroxyl equivalents of the oligomeric diol does not exceed the number of alcohol hydroxyl equivalents of the low molecular weight polyol, and stirred and mixed at room temperature to obtain a curing agent;

[0049] b) Compounding, pouring and curing of curing system:

[0050] b1) putting the fluorescent polyurethane prepolymer into a mixer equipped with a stirrer and a vacuum pump, adding a curing agent at room temperature, stirring rapidly, and stirring for 3 minutes while vacuuming, and the overall mixing and stirring time is controlled within 10-15 minutes;

[0051] b2) pouring the stirred mixture into a square plate cavity mold with a thickness of 1-6 mm, placing the mold in a vacuum-capable closed container, evacuating the container for 30-60 minutes, and curing at room temperature (25-40° C.) for 20-72 hours;

[0052] b3) The mold is then heated to 60° C., cured for 2 hours, naturally cooled to room temperature for 6 hours, and then heated to 80° C. for 1 hour. The mold is cooled and demoulded, and the burrs are repaired and the defects are cleaned to obtain a thermosetting polyurethane neutron conversion screen.

[0053] Furthermore, the low molecular weight polyol includes glycerol, triethanolamine or a combination thereof.

[0054] Furthermore, the curing agent contains multifunctional polyols and long-chain diols, which have the function of adjusting the reaction speed and reducing the viscosity of the curing system, thereby facilitating rapid degassing.

[0055] The invention provides a thermosetting polyurethane neutron conversion screen, which is characterized in that the thermosetting polyurethane neutron conversion screen is obtained according to a preparation method of the thermosetting polyurethane neutron conversion screen.

[0056] Furthermore, the thickness of the thermosetting polyurethane neutron conversion screen is 0.5-0.8 mm. The greater the thickness, the higher the brightness, and the lower the resolution. Vice versa. Under the condition that the composition of the fluorescent polyurethane functional material is certain, the optimal balance between resolution and sensitivity can be adjusted by adjusting the thickness of the conversion screen.

[0057] Example 1

[0058] Quantitatively weigh 12g (0.006mol) of PPG2000, 0.22g of dodecyltrimethoxysilane, 15.78g of ZnS:Ag, 0.6g of tetrahydrofuran, 0.015g of antioxidant 1010, and catalyst dibutyltin dilaurate (DBTDL) in a beaker, which have been dehydrated by vacuum at 110°C for 1 hour, and are fully stirred for 1 hour by a high-speed disperser, and then transferred to a 100ml three-necked flask, and then weigh 2.83g (0.01275mol) of IPDI is added to the three-necked flask, stirred at room temperature for half an hour, and then reacted at 60°C for 2 hours, and then the solvent THF is removed by vacuum to obtain a composite prepolymer of zinc sulfide / polyurethane in-situ polymerization. After cooling the temperature to 40°C, 0.5967 triethanolamine (TEOA) and 0.12g of PPG2000 solution dissolved in 1.5ml of THF solvent are added, and the stirring reaction is continued for 5 minutes. After stirring, ultrasonic treatment for 10 minutes was performed to remove most of the bubbles, and then a vacuum oil pump was used to further remove the tetrahydrofuran solvent and bubbles in the product. After completion, the product was poured into a polytetrafluoroethylene round plate, left at room temperature for 24 hours, and then placed in a vacuum oven at 60°C for 6 hours. After the last 6 hours, it was cured in an oven at 80°C for 1 hour. After cooling and demolding, a thermosetting polyurethane conversion screen with a zinc sulfide content of 50% and a thickness of 2 mm was obtained. Figure 1 Schematic diagram of the fluorescence spectra of ZnS:Ag, PU and ZSPU in Example 1 of the present invention.

[0059] Example 2

[0060] Quantitatively weigh 12g (0.006mol) of PPG2000, 0.22g of dodecyltrimethoxysilane, 3.67g of ZnS:Ag2, 1.0g of tetrahydrofuran, 0.015g of antioxidant 300, and catalyst dibutyltin dilaurate (DBTDL) in a beaker, which have been dehydrated by vacuum at 110°C for 1 hour, and are fully stirred for 1 hour by a high-speed disperser, and then transferred to a 100ml three-necked flask, and then weigh 2.83g (0.01275mol) of IPDI is added to the three-necked flask, stirred at room temperature for half an hour, and then reacted at 60°C for 2 hours, and then the solvent THF is removed by vacuum to obtain a composite prepolymer of zinc sulfide / polyurethane in-situ polymerization. After cooling the temperature to 40°C, 0.5967 triethanolamine (TEOA) and 0.12g of PPG2000 solution dissolved in 1.5ml of THF solvent are added, and the stirring reaction is continued for 5 minutes. After stirring, ultrasonic treatment for 10 minutes was performed to remove most of the bubbles, and then a vacuum oil pump was used to further remove the tetrahydrofuran solvent and bubbles in the product. The product was poured into a polytetrafluoroethylene round plate, left at room temperature for 24 hours, then placed in a vacuum oven at 60°C for 6 hours, and finally placed for 12 hours, and then cured in an oven at 80°C for 0.5 hours. After cooling and demolding, a thermosetting polyurethane conversion screen with a zinc sulfide content of 60% and a thickness of 2 mm was obtained.

[0061] Example 3

[0062] Quantitatively weigh 12g (0.006mol) of PPG2000, 0.22g of dodecyltrimethoxysilane, 1.56g of ZnS:Ag3, 2g of tetrahydrofuran, 0.015g of antioxidant 1010, and catalyst dibutyltin dilaurate (DBTDL) in a beaker, which have been dehydrated by vacuum at 110°C for 1 hour, and are fully stirred for 1 hour by a high-speed disperser, and then transferred to a 100ml three-necked flask, and then weigh 2.83g (0.01275mol) of IPDI is added to the three-necked flask, stirred at room temperature for half an hour, and then reacted at 60°C for 2 hours, and then the solvent THF is removed by vacuum to obtain a composite prepolymer of zinc sulfide / polyurethane in-situ polymerization. After cooling the temperature to 40°C, 0.5967 triethanolamine (TEOA) and 0.12g of PPG2000 solution dissolved in 1.5ml of THF solvent are added, and the stirring reaction is continued for 3 minutes. After stirring, use a vacuum oil pump to further remove the tetrahydrofuran solvent and bubbles in the product. After completion, pour the product into a polytetrafluoroethylene round plate, place it at room temperature for 48 hours, then place it in a vacuum oven at 60°C for 8 hours, and finally place it for 6 hours and then place it in an oven at 80°C for 1 hour. Cool and demould to obtain a thermosetting polyurethane conversion screen with a zinc sulfide content of 67% and a thickness of 2mm.

[0063] Example 4

[0064] Quantitatively weigh 12 g (0.006 mol) of PPG2000 that has been vacuum-dehydrated at 110°C for 1 hour, 0.22 g of dodecyltrimethoxysilane, 47.35 g of ZnS:Ag, 4 g of tetrahydrofuran, 0.015 g of antioxidant 1010, and 0.005 g of catalyst dibutyltin dilaurate (DBTDL) in a beaker, stir thoroughly for 1 hour with a high-speed disperser, transfer the mixture into a 100 ml three-necked flask, then weigh 2.83 g (0.01275 mol) of IPDI and add it to the three-necked flask, stir at room temperature for half an hour, then react at 60°C for 2 hours, and then remove the solvent THF in vacuo to obtain a composite prepolymer of zinc sulfide / polyurethane in-situ polymerization. After cooling down to 40°C, add 0.5967 triethanolamine (TEOA) and 0.12g PPG2000 solution dissolved in 2.5ml THF solvent, and continue stirring the reaction for 3min. After stirring, use a vacuum oil pump to further remove the tetrahydrofuran solvent and bubbles in the product. After completion, pour the product into a polytetrafluoroethylene round plate, leave it at room temperature for 48 hours, then place it in a vacuum oven at 60°C for 8h, and finally place it for 6 hours and then cure it in an oven at 80°C for 1 hour. Cool and demould to obtain a thermosetting polyurethane conversion screen with a zinc sulfide content of 75% and a thickness of 2mm.

[0065] In Examples 5-8, the operation method is the same as in Example 1, and the thickness is changed to 0.5mm, 1.0mm, 1.5mm, and 3mm.

[0066] In Examples 9-12, the operation method is the same as in Example 2, but the thickness is changed to 0.5 mm, 1.0 mm, 1.5 mm, and 3 mm.

[0067] In Examples 13-16, the operation method is the same as in Example 3, and the thickness is changed to 0.5mm, 1.0mm, 1.5mm, and 3mm.

[0068] In Examples 17-20, the operation method is the same as in Example 4, and the thickness is changed to 0.5mm, 1.0mm, 1.5mm, and 3mm.

[0069] The relative brightness of the neutron conversion screens prepared by the methods of the above 20 embodiments is shown in Table 1. The brightness of the conversion screen of Embodiment 1 is compared with the brightness of the existing mixed-pressure neutron conversion screen. Figure 2 This is a schematic diagram of surface detection of the neutron conversion screen of Example 1 of the present invention and four neutron conversion screens in the prior art. Figure 3 The luminous brightness detection effect diagram of the neutron conversion screen of Example 1 of the present invention and four neutron conversion screens of the prior art, wherein F0, EVA, EP, PP, and ZSPU respectively represent the imported commercial neutron conversion screen, the domestic EVA conversion screen, the domestic EP (epoxy) conversion screen, the domestic PP conversion screen, and the thermosetting polyurethane conversion screen of Example 1. At the same time, the resolution of the thermosetting polyurethane conversion screen is equivalent to that of the existing neutron conversion screen of the same thickness. It can be seen that the thermosetting polyurethane conversion screen prepared by the in-situ polymerization method can maintain a relatively high resolution while greatly increasing the brightness and detection sensitivity. This is of great significance to improving the imaging quality in the field of neutron photography.

[0070] Table 1 Brightness analysis results of ZSPU with different contents and thicknesses

[0071]

[0072] The thickness of the neutron conversion screen of the present invention is 0.1-8.0 mm, and the most preferred thickness is 1.5-3.0 mm. The main function of the neutron conversion screen is to convert the spatial distribution of neutrons that cannot be directly detected into the spatial distribution of visible light that can be detected. The fluorescence generated by the luminescent material zinc sulfide in the conversion screen is weakened according to the law of inversely proportional to the square of the distance on the one hand, and is also attenuated by the absorption of the screen material itself on the other hand. Therefore, the thickness of the neutron conversion screen should be selected to achieve a balance between sensitivity (detection efficiency) and resolution. After a large number of theoretical calculations and experiments, it is determined that the thickness of the neutron conversion screen is 1.5-3.5 mm.

[0073] The present invention is described in detail above in combination with specific implementation methods and exemplary embodiments. The above description is exemplary, not exhaustive, and is not limited to the disclosed embodiments; the above description cannot be understood as limiting the present invention. Those skilled in the art understand that, without departing from the spirit and scope of the present invention, the technical solution of the present invention and its implementation methods may be subjected to a variety of equivalent substitutions, modifications or improvements, all of which fall within the scope of the present invention; the protection scope of the present invention shall be subject to the attached claims.

Claims

1. A method for preparing an in-situ polymerized fluorescent polyurethane prepolymer, characterized in that: The following steps are involved: a) Raw material pretreatment: Weigh a certain amount of polyether diol or polyester diol into a 250 ml three-necked flask, and use a water ring vacuum pump to evacuate and remove water at 110° C. for 1-2 hours; weigh a certain amount of silver-doped zinc sulfide phosphor ZnS:Ag, and place it in a vacuum oven at 80-100° C. and dry it for 1-2 hours; b) Preparation of pre-dispersion of oligomeric diols: Take a certain amount of processed silver-doped zinc sulfide phosphor ZnS:Ag and polyether diol or polyester diol, coupling agent, catalyst, antioxidant, dissolve them in a solvent, and fully disperse them in a high-speed disperser for 15-45 minutes to obtain a pre-dispersion of oligomeric diol, wherein the components are composed of the following weight percentages: c) Preparation of fluorescent polyurethane prepolymer: A quantitative amount of fluorescent polyurethane prepolymer is weighed at room temperature and put into a reactor equipped with a reflux condenser and a stirrer, and then a pre-dispersion of diisocyanate: oligomeric diol is put into diisocyanate at a molar ratio of 2.1-3.1:1.0, stirred at room temperature -40 DEG C for 1 hour, then slowly heated to 60-80 DEG C and stirred for reaction for 2-5 hours, and nitrogen protection is used during the reaction process; the reaction is terminated, and tetrahydrofuran in the reaction mixture is removed by reduced pressure distillation with a water ring vacuum pump to obtain an in-situ polymerized fluorescent polyurethane prepolymer.

2. The method for preparing the fluorescent polyurethane prepolymer by in-situ polymerization according to claim 1, characterized in that: The diisocyanate includes toluene diisocyanate, diphenylmethane diisocyanate, hydrogenated diphenylmethane diisocyanate, isophorone diisocyanate, hexamethylene diisocyanate, hexamethylene diisocyanate trimer, lysine diisocyanate or a combination thereof.

3. The method for preparing the fluorescent polyurethane prepolymer by in-situ polymerization according to claim 1, characterized in that: The diisocyanate is in excess of 5-55%.

4. The method for preparing the fluorescent polyurethane prepolymer by in-situ polymerization according to claim 1, characterized in that: The polyether diol or polyester diol includes ethylene glycol, propylene glycol, diethylene glycol, 1,4-butanediol, phthalic acid, adipic acid, halogenated phthalic acid, polyethylene glycol, polypropylene glycol, polytetrahydrofuran diol or polyester diol prepared by esterification reaction of phthalic anhydride or a combination thereof.

5. The method for preparing the fluorescent polyurethane prepolymer by in-situ polymerization according to claim 1, characterized in that: The silver-doped zinc sulfide phosphor ZnS:Ag includes silver-doped ZnS:Ag / Mn, ZnS:Ag / Cu, ZnS:Ag / Si or a combination thereof.

6. A method for preparing a thermosetting polyurethane neutron conversion screen using a fluorescent polyurethane prepolymer prepared by the method for preparing a fluorescent polyurethane prepolymer by in-situ polymerization according to any one of claims 1 to 5, characterized in that: The following steps are involved: a) Preparation of curing agent: The low molecular weight polyol, the solvent, and the oligomeric diol are mixed in a weight ratio of 1:(1-2) between the low molecular weight polyol and the solvent, and the number of alcohol hydroxyl equivalents of the oligomeric diol does not exceed the number of alcohol hydroxyl equivalents of the low molecular weight polyol, and stirred and mixed at room temperature to obtain a curing agent; b) Compounding, pouring and curing of curing system: b1) putting the fluorescent polyurethane prepolymer into a mixer equipped with a stirrer and a vacuum pump, adding the curing agent at room temperature, stirring rapidly, and vacuuming while stirring for 3 minutes, with the overall mixing and stirring time controlled within 10-15 minutes; b2) pouring the stirred mixture into a square plate cavity mold with a thickness of 1-6 mm, placing the mold in a vacuum-capable closed container, evacuating the container for 30-60 minutes, and curing at room temperature for 20-72 hours; b3) The mold is then heated to 60° C., cured for 2 hours, naturally cooled to room temperature for 6 hours, and then heated to 80° C. for 1 hour. The mold is cooled and demoulded, and the burrs are repaired and the defects are cleaned to obtain a thermosetting polyurethane neutron conversion screen.

7. The method for preparing a thermosetting polyurethane neutron conversion screen according to claim 6, characterized in that: The low molecular weight polyol includes glycerol, triethanolamine or a combination thereof.

8. The method for preparing a thermosetting polyurethane neutron conversion screen according to claim 6, characterized in that: The curing agent comprises a multifunctional polyol and a long-chain diol.

9. A thermosetting polyurethane neutron conversion screen, characterized in that: The method for preparing the thermosetting polyurethane neutron conversion screen is obtained according to any one of claims 6 to 8.

10. The thermosetting polyurethane neutron conversion shield according to claim 9, characterized in that: The thickness of the thermosetting polyurethane neutron conversion screen is 0.5-0.8 mm.

Citation Information

Patent Citations

  • Cubic crystal zinc sulfide nano-particles and nanocomposite optical thin film prepared thereby

    CN101817549A

  • Method for preparing quantum dot / polyurethane nano crystal composite

    CN101906249A

  • In-situ preparation of TPU light conversion luminous film

    CN104109225A

  • Polythiourethane-acrylic acid-zinc sulfide composite hydrogel material and its preparation method and use

    CN106065050A

  • Fluorescent waterborne polyurethane and preparation method thereof

    CN110330622A